CD4 down-regulation by nef alleles isolated from human immunodeficiency virus type 1-infected individuals. - Mariani, R (1993)
PCR was used to clone isolates of the human immunodeficiency virus type 1 (HIV-1) nef gene directly from peripheral blood leukocytes of HIV-1-infected individuals. A transient expression system with human CEM T cells was used to assess the effect of nef on CD4 antigen expression on the cell surface. We show that CD4 down-regulation is a frequent property of primary HIV-1 nef alleles. Mutations in conserved amino acid motifs of Nef disrupted CD4 down-regulation. Our observations strongly suggest that CD4 down-regulation reflects a conserved function of nef, which is selected in vivo in human HIV-1 infection. Methodology described here provides quantitative assays to establish whether alterations in nef correlate with the dynamics of disease progression in human AIDS.